Bridging the gap: ferroptosis of immune cells in the tumor microenvironment - Wang, Weijing; Li, Huiyao; Liang, Shuai; Hu, Yani; Ding, Junli; Wu, Xi; Hua, Dong (Frontiers in Immunology, 2025)
Ferroptosis, an iron-dependent form of regulated cell death driven by lipid peroxidation, is increasingly recognized as a pivotal immunomodulatory mechanism within the tumor microenvironment (TME). Beyond its well-established role in tumor cell elimination, emerging evidence reveals that immune cell subsets exhibit distinct susceptibility to ferroptosis, with profound consequences for antitumor immunity. This review systematically delineates the dual and cell-type-specific roles of ferroptosis across innate and adaptive immune populations: while ferroptosis-mediated depletion of immunosuppressive cells potentiates antitumor responses, immunostimulatory cells critically depend on ferroptosis defense pathways to sustain their survival and function—their dysfunction exacerbates immune evasion. We further decode the metabolic and signaling networks that govern immune cell ferroptosis and their dynamic interplay with immunotherapy and engineered nanomaterials. Finally, we critically addressed key challenges in clinical translation, including biomarker development, cell-specific delivery, and design of nanomaterials to minimize off-target effects. By elucidating the immune context-dependence of ferroptosis, this review provides a framework for developing precision therapies that harness ferroptosis-immune crosstalk to improve cancer therapy in the clinic.